Desain Alat Hitung Berbasis Angka Braille, Cube’s Sebagai Alternatif Baru Dalam Pembelajaran Matematika untuk Anak Berkebutuhan Khusus (Tuna Netra) - Pratiwi, Nani (Journal Evaluation in Education (JEE), 2022)
The aim of this research is to describe the design of a counting device based on braille numbers, cube’s as a new alternative in learning mathematics for children with special needs (blind). And knowing student responses to products in the form of braille number-based counting tools, cube’s for children with special needs (blindness) that are valid and practical. The development method used in this research is 4-D. The stages in 4-D are define, design, development, and desseminate. Braille numeral-based counting tools, cube’s have been made and then validated by a team of experts to be further tested on blind students to determine the level of feasibility of calculating equipment based on predetermined aspects. The results of the analysis of the media design validation obtained a percentage of 83.00% and in the good category while the student response in the trial showed an average percentage of 89.64% (very good). Based on the results of the calculations obtained in this study, it can be concluded that the design of a counting device based on Braille numbers, Cube’s is feasible to be used as a learning medium in learning mathematics for children with special needs majoring in A, namely children with visual impairments. This study strengthens the design of tools that can be used as an alternative to support mathematics learning in children with special needs.